Some Morphometric Traits of S. rivulatus (Forsskål, 1775) and S. luridus (Ruppel, 1828) in Derna coast, eastern Libya, Mediterranean Sea - Najiyah S. Husayn; Marwah A. F. Saeid (African Journal of Advanced Pure and Applied Sciences, 2025)
Sixty Siganus luridus fish and sixty Siganus rivulatus were collected from the artisanal catch of Derna coast, eastern Libya during March/April 2021 for use in the present study to established morphometric traits and descriptive characters for both fish. The morphometric trait corelated to each other and related to fish length as an indicator of fish growth and age by linear and power regression. Siganus luridus of the present study was larger than S. rivulatus. For example, the mean Total Weight (TW) of S. luridus was 105.65±5.40 g while that of S. rivulatus was 59.95±2.06 g. The mean of Total Length (TL) of S. luridus was 18.72±0.39 cm while that of S. rivulatus was 17.19±0.21 cm. The linear and power weight-length relationship for S. luridus were Y=10.22X-85.63, R2=0.54, Y=0.31X1.98, R2=0.63 while that of S. rivulatus were Y=6.895X-58.57, R2=0.51, Y=0.478X1.69, R2=0.46 for linear and power regression respectively. Both fish indicated negative allometric growth.